PERAN GURU PAI DALAM PEMBENTUKAN KARAKTER ISLAMI SISWA DI SMPN 03 JOMBANG - Zida Haniyyah (LP3M STIT Al Urwatul Wutsqo Jombang, 2021)
The formation of Islamic character in schools cannot be separated from the role of the Islamic Religious Education (PAI) teacher. Because Islamic Religious Education (PAI) teachers are figures, role models, idols for their students who are able to color students into Islamic characters through exemplary and habituation. The objectives of this study were: (1) to describe the role of the Islamic religious education teacher (PAI) in the formation of Islamic character of students at SMPN 3 Jombang. (2) Describing the Islamic Character of Students at SMPN 3 Jombang. This study used a qualitative descriptive research design. Data collection techniques using interview, observation, and documentation techniques. Furthermore, data analysis was carried out using qualitative descriptive analysis method, namely in the form of written data presentation regarding related data. The next step is to test the validity of the data by extending participation, observation persistence and triangulation. The results showed that the role of the Islamic Religious Education teacher in the formation of Islamic character of students at SMPN 3 Jombang as follows: the teacher as a guide, the teacher as an educator, the teacher as a motivator and the teacher as an evaluator. And the Islamic character of students at SMPN 3 Jombang is good, polite and courteous which is manifested by the enthusiasm of the students when participating in religious programs, accustomed to reading the Koran so as to form a character of love for the Qur'an, always polite to anyone, say honestly, be patient, enthusiasm in worship, salim greetings to the mother / father teacher when entering the gate which trains students to be polite, courteous and respectful to elders, obey Allah by praying in congregation, praying dhuha, praying before studying, Istighosah, commemoration of Islamic holidays, donations for orphans and extra al banjari.